Reconsidering a strategy-based instruction (SBI) to teaching and learning another language using transferrable language learning strategies within a sociocultural framework (2014)
Following the announcements concerning introducing and developing modern languages in Key Stage Two in England, although not a new initiative, prompted the need to train generalist primary trainee teachers in teaching modern languages. After the initial announcement of the introduction of the English Baccalaureate in the secondary school, the poor outcomes achieved by England in the European languages survey and the news that languages would be part of the primary curriculum contributed to refreshing the agenda of languages in a country where teaching and learning other languages are seen as an exception rather than the norm. In order to provide primary school trainee teachers with the skills necessary for teaching young learners languages at an ab-initio level, this paper focuses on increasing subject knowledge and pedagogical competence in a short time by developing trainees’ prior knowledge and reflective practice, broadly following the tradition of strategy-based instruction, but within a social constructivist understanding of learning. The purpose of this paper, therefore, is to review the theoretical perspectives of Chamot’s model to reinterpret it so that it accommodates the complexities of the learning environment, learners’ identity, their interactions in a community of practice as well as the demands of the context, but acknowledging the trainees’ prior linguistic knowledge, their knowledge of the world and their motivation for learning other languages, as we believe these are necessary conditions to consider when designing effective pedagogical interventions aimed at adult learners.